(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
From the analysis of a database constituted by notarial documentation of the 1st and 2nd Notary Offices of Uberaba, from 1861 to 1888, we seek to identify and characterize the main slave traders operating in that market, as well as their commercial strategies and connections established with other squares, aiming to understand who they were and how they acted, in the then main municipality of Triângulo Mineiro, some of those responsible for the large movements of workers operated by intra and interprovincial slave trades in the Empire of Brazil between the abolitions of the transatlantic slave trade (1850) and Slavery (1888). To do so, we also resorted to onomastic research in newspaper advertisements, almanacs and the work of the memoirist Antônio Sampaio.